Effect of Premature Rupture of Membranes on Induction of Labor: A Historical Cohort Study - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Baier, Friederike; Faschingbauer, Florian; Beckmann, Matthias; Suetterlin, Marc; Pretscher, Jutta (Geburtshilfe und Frauenheilkunde, 2017)
Objective: The aim of this study was to assess the influence of premature rupture of membranes (PROM) on the induction of labor. Material and Method: This historical cohort study analyzed 1861 inductions of labor at term using misoprostol which occurred between 2010 and 2015. Exclusion criteria included intrauterine fetal death, previous cesarean section, and fetal structural or chromosomal anomalies. Induction of labor for PROM (PROM group) was compared to induction for other indications (no-PROM group); the primary outcome measure was the cesarean section rate. Results: The cesarean section rate for the PROM group was significantly lower (21.9% vs. 26.3%, p = 0.029). The induction-to-delivery interval was shorter (mean: 972 [854 - 6734] min vs. 1741 [97 - 10 834] min, p < 0.0001) and the rates of vaginal birth within 24 hours (80.9 vs. 52.0%, p = 0.0001) and 48 hours (98.4 vs. 85.3%, p = 0.0001) were higher in the PROM group. The impact of PROM on the cesarean section rate was not significant in multivariate analysis; however, PROM was found to have the greatest effect on the induction-to-delivery interval (p < 0.0001). Conclusion: Premature rupture of membranes significantly affects various outcome measures when delivery is induced, particularly the induction-to-delivery interval.
EVALuna2:36121